PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK UNTUK MENGIDENTIFIKASI MISKONSEPSI PADA MATERI OPERASI BILANGAN BULAT - Cicih Sutiani; Linda Herawati; Redi Hermanto (Jurnal Karya Pendidikan Matematika, 2024)
This study aims to develop a valid and practical diagnostic test instrument so as to identify student misconceptions on integer operation material. Diagnostic tests are developed using a four-tier test format. The research method uses a development method by Tessmer, namely Formative Research which consists of the preliminary stage, self-evaluation stage, prototyping stage (expert review, one to one, small group) and field test stage. The results are diagnostic test instruments that are declared valid and practical by the experts and the students. The results of the student diagnostic test showed that there was a misconception in the Learning Objectives (TP) of reading and writing integers by 25.86%, comparing integers by 12.07%, performing arithmetic operations on integers by 21.94% and using arithmetic operations on integers and providing estimates in solving problems by 27.01%.